2018
DOI: 10.4265/bio.23.35
|View full text |Cite
|
Sign up to set email alerts
|

<i>In vitro</i> Inhibitory Effects of Two Bornean Medicinal Wild Gingers against Pathogenic <i>Lagenidium thermophilum</i> Infected Mud Crab <i>Scylla tranquebarica</i>

Abstract: The antifungal activity of two Bornean medicinal wild gingers Plagiostachys megacarpa and Zingiber phillippsiae were examined against Lagenidium thermophilum. The most active extract was P. megacarpa at concentration of 320 µg/mL inhibiting both hyphal growth and zoospore production of L. thermophilum in 24 h. Toxicity tests were conducted using mud crab Scylla tranquebarica larva. Bath treatment of P. megacarpa at concentrations of 320 and 640 µg/mL for 24 h were highly effective against hyphae and zoospores … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
1
Order By: Relevance
“…Ethanol and methanol extract show the lowest MIC at 100 mg/ml against marine oomycetes, L. thermophilum (Table 2). In contrast to previous studies by Hatai et al, (2018) showed that the wild ginger, Plagiostachys megacarpa extraction at a concentration of 320 μg/mL inhibited both hyphal growth and zoospore production of L. thermophilum in 24 h. MIC result from Figure 1 showed that the L. flava extraction had an inhibitory effect towards hyphal growth at 100 mg/mL which is lower compared to P. megacarpa which is 320 µg/mL. However, it is very difficult to direct comparison because reports on L. flava extracts against marine oomycetes species are very limited.…”
Section: Resultscontrasting
confidence: 81%
See 1 more Smart Citation
“…Ethanol and methanol extract show the lowest MIC at 100 mg/ml against marine oomycetes, L. thermophilum (Table 2). In contrast to previous studies by Hatai et al, (2018) showed that the wild ginger, Plagiostachys megacarpa extraction at a concentration of 320 μg/mL inhibited both hyphal growth and zoospore production of L. thermophilum in 24 h. MIC result from Figure 1 showed that the L. flava extraction had an inhibitory effect towards hyphal growth at 100 mg/mL which is lower compared to P. megacarpa which is 320 µg/mL. However, it is very difficult to direct comparison because reports on L. flava extracts against marine oomycetes species are very limited.…”
Section: Resultscontrasting
confidence: 81%
“…Previous studies reported that Cabomba aquatica leaves have antifungal effects due to the presence of secondary metabolites such as tannins, steroids, glycosides, flavonoids, phenolic compounds, and alkaloids (Malathy et al, 2015). Ginger Plagiostachys megacarpa that were extracted showed an antifungal effect against L. thermophilum IPMB 1401 (Hatai et al, 2018). Seaweed extracts are known for functional food and obtain bioactive compounds (Pal et al, 2014).…”
Section: Introductionmentioning
confidence: 99%